Numerical Evaluation of Unsaturated‐Zone Flow and Transport Pathways at Rainier Mesa, Nevada. Issue 1 (8th August 2019) - Kwicklis, Edward; Lu, Zhiming; Middleton, Richard; Miller, Terry; Bourret, Suzanne; Birdsell, Kay
Abstract : Core Ideas: Permeability contrasts in layered rocks can result in perched water and lateral flow. Diversion of water above the testing horizon slows the downward transport of radionuclides. Permeable rocks within saturated rocks of lower permeability can remain unsaturated. Sixty‐one underground nuclear tests were conducted at Rainier Mesa at the Nevada National Security Site between 1957 and 1992. The mesa includes the highest‐elevation areas at the Nevada National Security Site and experiences some of the highest estimated infiltration rates. Perched water is ubiquitous in many of the tunnels used for testing. The presence of sloping layers with strongly varying degrees of fracturing and overall permeability suggests that some infiltrating water may be diverted laterally along higher‐permeability layers, thereby reducing overall percolation flux and radionuclide transport through the low‐permeability testing horizons but also potentially transporting radionuclides laterally away from the test locations. A high‐resolution, two‐dimensional, cross‐sectional model was created to simulate water and particle movement along potential lateral flow paths and to investigate flow and transport paths within and surrounding the perched water bodies. The model results indicate that particles with starting locations within the low‐permeability perching layers will follow dominantly vertical trajectories through the perching horizons and reach the water table in the underlying carbonate aquifer only after many thousands of years. In contrast, particles starting near ground surface above the testing horizon are mostly diverted laterally before reaching the testing horizon, except where nearby faults through the perching layers are present. Where the rock above the perching horizon is fractured, particles originating near ground surface can move laterally with relatively high transport velocities. Transport calculations for 3 H show that transport extent is limited by slow matrix flow, radioactive decay, and matrix diffusion in the fractured units.